Efektivitas Terapi Aktivitas Kelompok terhadap Peningkatan Kemandirian Lansia - Ariyanti, Sri; Rasyid, Djusmadi; Rosida, Rosida (Barongko: Jurnal Ilmu Kesehatan, 2025)
Decreased physical and psychological abilities in the elderly often lead to a decreased level of independence in performing daily activities. Group activity therapy (GAT) is a nursing intervention aimed at improving the social, psychological, and independence abilities of the elderly through collaborative activities. This study aimed to determine the effectiveness of group activity therapy in increasing the independence of the elderly. The study used a quasi-experimental design with a pre-test, post-test, one-group design. The population in this study was all elderly people in nursing homes, with a sample of 30 people selected using a purposive sampling technique. The instrument used was an independence observation sheet based on the Katz Index of Independence in Activities of Daily Living (ADL). Data analysis used the Wilcoxon Signed Rank Test. The results showed a significant difference between the level of independence before and after group activity therapy (p = 0.000 < 0.05). Conclusion: Group activity therapy is effective in increasing the independence of the elderly. This intervention is recommended as a routine activity program in nursing homes and community settings.